Diversity of Herpetofauna in Kadamaian, Kota Belud, Sabah, Malaysia - Anna Wong @ Wong Yun Moi; Nur Syamimi Makbul; Paul Yambun (Universiti Malaysia Sabah, 2021)
A survey on amphibians and reptiles or herpetofauna in Kadamaian, Kota Belud was carried out on 21st to 25th October, 2019 during the Borneo Geographic Expedition jointly organized by the Institute for Tropical Biology and Conservation (ITBC) of Universiti Malaysia Sabah (UMS) and Sabah Parks. The main purpose of the survey is to update the list of herpetofauna in the study area. Visual Encounter Survey (VES) method was applied and transects were established at the waterfall near the expedition base camp, Pinolobu River, Kipungit River in Melangkap Noriou and Meliawa River, resulting in 15 species of amphibians from five families and six species of reptiles from three families recorded. Significantly, the survey recorded 10 species of herpetofauna that are endemic to Borneo, including one Endangered (EN) frog species namely Leptobrachella sabahmontana of the family Megophryidae and one new record for Sabah which is Ansonia minuta of the family Bufonidae. Two reptiles out of the recorded list were Bornean endemics namely Cyrtodactylus baluensis and Tropidophorus micropus. Fejevarya limnocharis and Polypedates leucomystax seemed to be the common species of amphibians recorded whereas Eutrophis rudis was the common reptile species found in the area. The result, in term of species number was low especially for reptiles due to the short survey period. However, this report managed to update the list for herpetofauna species in Kadamaian, Kota Belud. Nevertheless, this study contributes to Borneo’s herpetofauna database specifically in Sabah and serves as reference for more studies and research in future.